ANALISIS TINGKAT KESEHATAN BANK DENGAN CAMEL RATIO DAN MEKANISME CORPORATE GOVERNANCE DALAM MEMPREDIKSI FINANCIAL DISTRESS PERBANKAN INDONESIA - Jamaluddin Jamaluddin; Anisatun Kamilah (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2018)
The purpose of this research is to analyze bank soundess with the camel ratio and corporate governance mechanism in forcasting financial distress for Indonesian Banking. The dependent variable is financial distress whereas the independent variable that is used in this research is Camel ratio variable and proxy to be six financial ratio such as Current Adequacy Ratio (CAR), Non Performing Loan (NPL), Return On Equity (ROE), Loan to Deposit Ratio (LDR), Biaya Operaional Pendapatan Operasional (BOPO), Net Interrest Margin (NIM) and Corporate Governance variabel proxy by Size of Board Commissioners, Size of Board Director and Independent Commissioners. The sample of this research is using purposive sampling method. The sample obtained as many as 174 companies bank which is devided by 2 category: 155 banking there are “no problem” and 19 banking have “problem”. Sample of this research in the secondary data who listing in Indonesian Stock Exchange during period 2011-2016. Logistic regression in statistic method used by hypothesized research. The result of this research shows that Camel ratio variabel such as capital adequacy is measured by CAR has negative influence to financial distress, asset quality is measured by NPL has positive influence to financial distress, profitability is measured by ROE has negative influence to financial distress, liquidity is measured by LDR has positive influence to financial distress, efficiency is measured by BOPO has positive influence to financial distress and operating profit is measured by NIM has negative influnce to financial distress and also corporate governance variable proxy by Size of Board Commissioners has negative influence to financial distress, Size of Board Director has negative influence to financial distress and Independent Commissioners has negative influence to financial distress of this research.Key Words: Camel ratio, good corporate goernance, financial distress and bankruptcy